Debitus grisailles for stained-glass conservation: an analytical study - Machado, Carla (2020)
Grisaille is one of the oldest and most widely used vitreous paint applied for the production of stained-glass panels and Debitus is one of the most renowned commercial brands whose grisailles are frequently used for the chromatic reintegration in stained-glass window restoration. This article presents the morphological, chemical and thermal analyses of five grisailles from Debitus, to evaluate their properties before and after firing with the objective of knowing their future stability. The characterisation was carried out by optical microscopy, scanning electron microscopy, particle induced X-ray emission, X-ray diffraction, and infrared thermography. This study showed a well-balanced ratio between the different components and a good interdiffusion into the glass, as well as a consistent thermal behaviour between them and with the glass, which indicates the good stability and durability of these materials.   Received: 2018-12-9 Revised: 2019-4-5 Accepted: 2019-4-29 Online: 2019-5-17 Publication: 2020-7-31